Como nuevo - Douglass, Barbara, 1930-; Brewster, Patience (New York : Scholastic Inc., 1993)
When Grady's young cousin ruins his teddy bear, Grandpa promises to fix the toy.
Translation of: Good as new.
Keywords: Toys -- Fiction; Grandfathers -- Fiction; Teddy bears -- Fiction; Spanish language materials -- Fiction